Functional Cell Adhesion Receptors (Integrins) in Polymeric Architectures. Issue 12 (14th July 2015) - Zaba, Christoph; Ritz, Sandra; Tan, Cherng‐Wen Darren; Zayni, Sonja; Müller, Martina; Reuning, Ute; Sinner, Eva‐Kathrin
Abstract Integrins, as transmembrane heterodimeric receptors, have important functions in cell adhesion, migration, proliferation, survival apoptosis and signal transduction, in many physio‐ as well as pathophysiological settings. Characterisation of integrins and their ligand/antagonist binding is notoriously difficult, due to high integrin redundancy and ubiquity. Bypassing the intrinsic difficulties of cell‐based integrin expression, purification and reconstitution, we present for the first time the synthesis of a heterodimeric integrin receptor and its assembly into a block‐copolymeric membrane mimic. We present comprehensive data to demonstrate the synthesis of functionally active integrin αvβ3, generated by in vitro membrane‐assisted protein synthesis (iMAPS). This work represents the first step towards a robust and adaptable polymer‐based platform for characterisation of integrin–ligand interactions.